Factors influencing the quality of consecutive interpretation from the perspective of interpreter - Chunli, Yu; Mansor, Nor Shahila; Ang, Lay Hoon; Sharmini, Sharon (Human Resource Management Academic Research Society, 2021)
This study examines the factors influencing the quality of consecutive interpretation based on an interview of a skilled interpreter. The data for this research is mainly collected from a semi-structured interview. This study is a descriptive qualitative study, aiming to have an in-depth analysis of interpretation. The analysis of the data is under the framework proposed by Andrew Gillies (2019). The findings revealed several factors that influence the quality of interpretation, such as techniques on taking note, quick response, culture elements & theoretical foundation. In order to respond quickly, the interpreters should make enough preparation, make quick decisions on word choice, practice more and keep constant learning. The findings have implications on the understanding of consecutive interpretation, which could offer some practical guidance for the prospective interpreters. Moreover, the findings of the study in consecutive interpretation will help enhance business negotiations and promote cross-culture communication.